Financial Literacy and MSME Performance: Mediation and Moderation Analysis - Hererra, Juan Jose Duran; Warokka, Ari; Aqmar, Aina Zatil (TALENTA PUBLISHER UNIVERSITAS SUMATERA UTARA, 2023)
This research examines the mediating role of access to finance, financial risk management, and competitive advantage in the relationship between financial literacy and Micro, Small, and Medium Enterprises (MSME) performance. This research also tests demographic factors such as the owner's gender, company size, company age, and number of employees in moderating the influence of the variables studied. The sample for this research is MSMEs in Jakarta Province, Indonesia. Five hundred and fifty MSMEs participated in the study using a web-based self-administered questionnaire. The data was analyzed using Partial Least Square Structural Equation Modeling (PLS-SEM). The research results show that financial literacy positively affects access to finance, financial risk management, competitive advantage, and MSME performance. Access to finance, financial risk management, and competitive advantage positively affect MSME performance and can mediate the relationship between financial literacy and MSME performance. The research also uncovers the moderating role of demographic factors, suggesting that the strength of the connections between financial literacy, access to finance, financial risk attitude, competitive advantage, and MSME performance may vary based on these factors. These findings carry significant implications for owners, managers, and governmental stakeholders, emphasizing the importance of enhancing financial literacy among MSMEs to enhance their performance.